DEVELOPMENT POTENTIAL OF MEDICINAL PLANTS OF RURAL AREAS - Kostadinović, Ljiljana; Ružičić, Lazar; Galonja-Coghill, Tamara; Lević, Jovanka; Pavkov, Sava (Economics of Agriculture, 2011)
The area of Serbia is characterized by a large diversity of flora (over 3500 species and subspecies), and thus the wealth of natural resources of medicinal and aromatic plants (more than 700 species are used in ethnomedicine). Serbia, due to favorable climate, soil and unpolluted environment is very suitable for intensive cultivation of medicinal plants, and this type of production made bigger, faster and easier profts than other agricultural production and as such represents a great opportunity for development, primarily in rural areas in Serbia. Sustainable development of natural resources of medicinal and aromatic plants is directly dependent on the application and improvement of legislation and standards that must be harmonized with EU legislation and standards. Regardless of the great opportunities that the herbal sector has on the countryes economic system, many resources, especially when it comes to exports, the higher stages of processing and cultivation, ie. cultivation of medicinal plants (especially on the principles of organic agriculture), are anused.